The role of the integration of financial control agencies in improving the quality of auditing A case study of the College of Pharmacy of Howler Medical University - Aram Farhad Ali (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study examined the role of the integration of financial control agencies in improving the quality of auditing, a case study of the College of Pharmacy of Howler Medical University, where it aimed to achieve quality in audit work through the integration of the performance of both the financial auditor and the internal auditor in cooperation and coordination between them, and the study assumed that integration contributes to The financial watchdog worked to improve control work and achieve audit quality, and the study used the descriptive analytical approach to describe and analyze the phenomenon and after the analysis using the statistical packages program (SPSS), the study concluded that the requirements currently available to implement internal audits are not sufficient to develop T quality audit services such as brochures illustrations, training sessions, meetings, seminars, etc. ... The results and supervision of professional organizations specialized in the work of supervision and auditing are currently not at the level required to ensure the provision of forms and areas of cooperation and coordination between both the financial auditor and the internal auditor and thus achieving quality in the audit